Hazarat Hud (AS) - Karam , Ambia (Lahore ' Karachi Children's publication)
Hud (as) was a descendent of Sam and sent as a prophet to the people of Aad. The name Hud comes from the Arabic word hawadah, which means softness, calm, peace and any means that gives a person these qualities. Hud (as) was also known as Abir, as well as Nabiyyullah, Allah's prophet.